LncRNAs SOX2-OT and NEAT1 act as a potential biomarker for esophageal squamous cell carcinoma - Rajiv Ranjan Kumar; Adrija Mohanta; Manjit Kaur Rana; Vivek Uttam; Hardeep Singh Tuli; Aklank Jain (Discover Oncology)
Abstract Despite strides in diagnostic and therapeutic approaches for ESCC, patient survival rates remain relatively low. Recent studies highlight the pivotal role of long non-coding RNAs (lncRNAs) in regulating diverse cellular activities in humans. Dysregulated lncRNAs have emerged as potential diagnostic indicators across various cancers, including ESCC. However, further research is necessary to effectively leverage ESCC-associated lncRNAs in clinical settings. Understanding their clinical significance for ESCC diagnosis and their mechanisms can pave the way for more effective therapeutic strategies. Our qRT-PCR analysis revealed significant downregulation of SOX2-OT (~ 2.02-fold) and NEAT1 (~ 1.53-fold) in ESCC blood samples. These lncRNAs show potential as biomarkers for distinguishing ESCC patients from healthy individuals, with ROC curves and AUC values of 0.736 for SOX2-OT and 0.621 for NEAT1. Further analysis examined the correlation between SOX2-OT and NEAT1 expression and various clinicopathological factors, including age, gender, smoking, alcohol use, hot beverage intake, tumor grade, and TNM stages. In-silico studies highlighted their roles in miRNA sponging via mTOR and MAPK pathways, while co-expression network analysis identified associated genes. This research paves the way for future studies on ESCC prognosis using SOX2-OT and NEAT1 as predictive markers. By thoroughly investigating the functions of these lncRNAs, we aim to deepen our understanding of their potential as diagnostic markers and their role in facilitating effective therapeutic interventions for esophageal squamous cell carcinoma (ESCC) within clinical contexts.